THE INTEGRATION OF CHARACTERS EDUCATION INTO TEACHING READING HORTATORY TEXT - Meladina; Amir, Zainuddin (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
AbstractThis paper describes how to implement the character education in the classroom byusing the reading skill hortatory exposition text. At the beginning of the lesson, theteacher has to model one of the characters that the students have to adopt then to makethe students think creatively, the teacher shows a picture and asks them to share theirideas about it. After that, the teacher distributes a hortatory text that related to thepicture and consists of character education on it. The teacher guides the students tocomprehend the text and discuss what the text tells about. The teacher also introducessome character education on his/her steps of teaching. To make the students moreunderstand about the text, the teacher asks the students to work in pair to make asummary writing about the text and repot it in front of the class.by using their ownwords. Key Words: Character Education, Reading, Hortatory Text